Sensitizing Teachers and Students on Group Work and Cooperative Learning as Techniques for Writing Teaching Quality - KESKES, Said (Journal of Human Sciences, 2009)
The present study attempts to promote Cooperative learning (CL) through group work by exploring teachers’ and students’ attitudes and readiness towards the introduction of theses techniques, as innovating tools for teaching writing. Promoting these techniques seeks to provide potential improvements in the teaching of writing to face unsatisfaction manifested amongst teachers and students. This paper is exploratory and descriptive in orientation, with no experimental purpose, which in our opinion, could happen only when the promotion of the suggested techniques receives a positive echo from the stakeholders. The study has concerned second year students of English, and teachers of writing. To this end, 56 students and 06 teachers of written expression modules took part in the study. If the study should show the worthiness to introduce these writing techniques for potential better teaching through teachers’ and students’ attitudes; then, it may be proposed as a recommendation for implementation. Some notions and raising approaches for teaching this writing skill have to be presented as well as aspects of some categories of CL activities and their application to language learning. To evaluate this, we conduct a descriptive approach. Students and teachers had been given questionnaires to be answered. The results show that the teachers and the students have reacted positively to the suggestions introduced in the questionnaires of these writing teaching techniques, for their teaching/learning potential advantages. This leads us to believe that classrooms teaching/learning problems when identified might be apprehended collectively by teachers, students and specialists by putting forward remedial techniques for their latent pedagogical efficiency before being even proposed for application. This is one of the canons of action research where teachers and students should be allowed to voice opinions even on materials they have to learn a language with.